Lithium-bearing Cambrian Fluidolites of the Angaro-Lena Foredeep, South Siberian Platform - M. I. Tyumentseva; N. I. Akulov; A. I. Melnikov (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
This paper presents the results of a study of the Lower Cambrian halogen-carbonate deposits of the Angara-Lena foredeep (the southern part of the Siberian platform). It was found that they contain large masses of fluidolites and strata of chemogenic rocks hosting volcanogenic material. Besides, the presence of pyroclastic matter has been recorded in both carbonate and evaporite deposits. Fluid-explosive activity within the Early Cambrian shallow epicontinental sea occurred during catastrophic events caused by phreatomagmatic activity. It is noted that most of the volcanogenic material is concentrated near the foci of volcanic activity, and only a small part of it was carried away by underwater currents and deposited in the form of volcanogenic-chemogenic strata, serving as marking horizons. It was found that the formation of chemogenic deposits containing tuffogenic material occurred simultaneously with the hydrothermal emissions of volcanic systems such as black smokers, which led to the formation of volcanogenic sedimentary deposits rich in lithium oxides and other rare earth elements.